2017
DOI: 10.1038/srep43694
|View full text |Cite
|
Sign up to set email alerts
|

Facile approach to fabricate waterborne polyaniline nanocomposites with environmental benignity and high physical properties

Abstract: Waterborne polyaniline (PANI) dispersion has got extensive attention due to its environmental friendliness and good processability, whereas the storage stability and mechanical property have been the challenge for the waterborne PANI composites. Here we prepare for waterborne PANI dispersion through the chemical graft polymerisation of PANI into epichlorohydrin modified poly (vinyl alcohol) (EPVA). In comparison with waterborne PANI dispersion prepared through physical blend and in situ polymerisation, the sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…In most studies involving preparation of PANI blends or composites, PANI was used as filler material, which reduces the surface conductivity of the blend at micro level. Therefore, in order to prepare PANI blends with uniform and enhanced conductivity at micro level, researchers have opted for in situ polymerization technique (Lu et al, 2007;Arenas et al, 2014;Pour-Ali et al, 2014;Wang et al, 2017). In this regard we tried preparation of PANI/Sago blends using in situ polymerization technique.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies involving preparation of PANI blends or composites, PANI was used as filler material, which reduces the surface conductivity of the blend at micro level. Therefore, in order to prepare PANI blends with uniform and enhanced conductivity at micro level, researchers have opted for in situ polymerization technique (Lu et al, 2007;Arenas et al, 2014;Pour-Ali et al, 2014;Wang et al, 2017). In this regard we tried preparation of PANI/Sago blends using in situ polymerization technique.…”
Section: Introductionmentioning
confidence: 99%
“…The two peaks often combined into a flat or distorted peak. The absorption band at 800 nm is taken as evidence of the presence of localized polarons/bipolarons [28]. Similar absorption peaks are observed in the imprinted polyaniline nanoparticles.…”
Section: Electronic Spectramentioning
confidence: 57%
“…S7. The spectra for the nonimprinted polyaniline shows absorption peak at 350 nm and 430 nm are ascribed to the   * transitions in the benzoid rings and exciton absorption in the quinoid rings [26][27][28][29][30]. The two peaks often combined into a flat or distorted peak.…”
Section: Electronic Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that building chemical bond between two materials is beneficial to improve their compatibility, processability and the related performance . In our previous study, it is also demonstrated that the introduction of A‐ g ‐B may be able to enhance the compatibility between A and B.…”
Section: Introductionmentioning
confidence: 85%